2020
DOI: 10.1002/jcla.23203
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of PCR‐based point‐of‐care diagnostic in respiratory tract infections in children

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: Children are commonly affected by respiratory tract infections. Based on clinical symptoms, laboratory evaluation, and imaging, the causative pathogen often cannot be delineated. Point-of-care-testing systems tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… 20 , 21 , 22 There have been 2 earlier RCTs investigating the impact of testing for multiple respiratory pathogens in acutely ill children (eTable 2 and eTable 3 in Supplement 2 ). 14 , 23 , 24 , 25 , 26 Rapid testing of 204 children for 7 respiratory viruses using a direct immunofluorescence assay significantly reduced the prescription of antibiotics after discharge from the ED, 14 although, in a recently published RCT involving 908 children with influenza-like illnesses, the use of rapid respiratory pathogen testing in the pediatric ED did not reduce the overall prescribing of antibiotics. 27 Moreover, the accompanying intention-to-treat analyses showed that children subjected to rapid multipathogen testing were even more likely to receive antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 , 22 There have been 2 earlier RCTs investigating the impact of testing for multiple respiratory pathogens in acutely ill children (eTable 2 and eTable 3 in Supplement 2 ). 14 , 23 , 24 , 25 , 26 Rapid testing of 204 children for 7 respiratory viruses using a direct immunofluorescence assay significantly reduced the prescription of antibiotics after discharge from the ED, 14 although, in a recently published RCT involving 908 children with influenza-like illnesses, the use of rapid respiratory pathogen testing in the pediatric ED did not reduce the overall prescribing of antibiotics. 27 Moreover, the accompanying intention-to-treat analyses showed that children subjected to rapid multipathogen testing were even more likely to receive antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference in oseltamivir prescription was noted when comparing FA-RP to the standard test (OR = 0.70, 95% CI 0.22–2.24, p = 0.55; I 2 = 84%) ( Figure 6 A) [ 32 , 33 , 46 , 48 , 51 ], which is confirmed in the sub-group analysis stratified by country (Europe and the US, see Figure S4A ). When comparing the use of FA-RP vs. clinical diagnosis of influenza [ 38 , 47 , 49 ], there was an increased trend in prescriptions but without a significant difference (OR = 2.94, 95% CI 0.48–17.86, p = 0.24; I 2 = 95%) ( Figure 6 B).…”
Section: Resultsmentioning
confidence: 60%
“…When comparing the use of FA-RP vs. standard test, an overall reduction in antibiotic prescriptions was noted (OR = 0.59, 95% CI 0.37–0.92, p = 0.02) [ 32 , 33 , 37 , 40 , 41 , 46 , 51 ], however, with a high heterogeneity (I 2 ) of 89% ( Figure 4 A). In a subgroup analysis stratified by countries, this reduction was more significant in the studies conducted in the US compared to Europe and East Asia (see Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a high C-reactive protein (CRP) level may be noted which can often lead to unnecessary use of antibiotics and hospital admissions. Using of point-of-care (POC) testing for HAdV infections could improve the pre-hospital evaluation, provide the diagnosis, and lead to appropriate therapeutic decisions [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%